A performance-based planning approach integrating supply and demand of urban ecosystem services - Cortinovis, Chiara; Geneletti, Davide (Landscape and urban planning, 2020)
[Display omitted] •A performance-based planning approach is built around urban ecosystem services.•Ecosystem service assessments define requirements for urban transformations.•The level of performance depends on the impacts on ecosystem service supply.•The type of performance depends on ecosystem service demand.•The approach is tested on different types of urban transformations. Performance-based planning is advocated as a promising alternative to more common prescriptive approaches (e.g., traditional zoning), to manage the complexity of current urban development in a flexible and effective way. The aim of this paper is to develop and test an innovative performance-based planning approach built around the assessment of ecosystem service supply and demand. The approach moves from the overall objective of enhancing the provision of relevant ecosystem services in the city. Accordingly, proposed urban transformations are subject to a performance assessment aimed at limiting the negative impact on the current ecosystem service supply and promoting the integration of ecosystem-based actions. The loss in the current supply defines the required level of performance, while the type of performance (i.e. what ecosystem services should be targeted) depends on ecosystem service demand. To support the implementation of the approach, we developed two operational tools: the “combined ES supply” map and the “integrated ES demand” map. A scoring system links the indicators in the two maps and assesses the balance between positive and negative impacts. The proposed approach is tested in the city of Trento, Italy, considering seven urban ecosystem services and three different types of urban transformations. The application reveals strengths and limitations, and offers a proof-of-concept that can be further refined and adapted to other contexts. The study demonstrates how ecosystem service assessments can support the design of technical policy instruments, thus contributing to filling a blindspot on the roles of ecosystem service knowledge in decision-making processes.